Picture Card Game Against Development Vocabulary in Early Childhood - Fitriani; Herlina; Herman; Wahira; Surya (CV Kalimasada Group, 2026)
Purpose – This study aims to (1) find out the description of vocabulary ability in the control group and the experimental group before and after treatment in the study of the influence of picture card games and to find out if there is a significant difference in vocabulary development in the children of the experimental group and the control group who have participated in the activity. Design/Methodology/Approach – This type of research uses a quantitative quasi-experiment with a pretest-posttest control group design. Data collection techniques are in the form of vocabulary tests (pre-test and post-test), observation of children's activities while playing drawing cards, and documentation (photos of activities, teachers' diaries). Data analysis techniques consist of; (a) Normality test, (b) Homogeneity test, (c) Hypothesis test. Findings – The results of the study showed that the learning method of picture card games was carried out with 4 treatment activities using picture card media which was made and then played by children in stimulating the visual vocabulary of children aged 5-6 years., the visual skills of children aged 5-6 years showed significant changes in children's visual abilities, before and after being given learning with pretest picture card media, obtained an average score of 9.6 while from the post-test results obtained an average score of 10.8., there was a significant influence on the vocabulary learning method with picture card media on the visual ability of children aged 5-6 years, this was shown based on the results of the Wilcoxon Sign Rank test. Originality/Value –This research provides alternative vocabulary learning media that is fun and effective, improves language skills in a more natural and fun way, and is a reference for further research on game-based learning media.